TEKNIK PENYUTRADARAAN DENGAN MENGOPTIMALKAN VISUAL DRAMATIK DALAM PRODUKSI PROGRAM DOKUMENTER “LENTERA” - Dhinda Martina, Oktafiani Herlina, Arif Budiman (AKADEMI KOMUNIKASI RADYA BINATAMA, 2019)
ABSTRACTLentera is the title of a documentary that tells about the children who living withHIV/AIDS. Where these children live in a foundation special for children with HIV/AIDS calledLentera Foundation. This documentary is not only tells about the live of children with HIV/AIDS,but also gives informations to the audience what is HIV/AIDS, HIV transmission, and how totreat HIV. In this documentary the human interest side will be more highlighted. The dramaticalvisual and storyline making this documentary an interesting movie.The selection theme about HIV/AIDS is an anti-mainstream and HIV/AIDS also a big issuein Indonesia nowadays. This issue certainly will attract the audience to watch thisdocumentary. With the right illustration music and suitable with the visual will more dramatizethe scene. Even though use the illustration music, but the sound of ambience still audible.Director is a person who directs a program that is involved in the creative process from pre topost production, both for drama and non drama. The director is fully responsible for theproduction process and in charge of leading the production.Keywords: Documentary, Director, Lentera